2020
DOI: 10.1186/s40734-020-00090-x
|View full text |Cite
|
Sign up to set email alerts
|

AbobotulinumtoxinA using 2-mL dilution (500 U/2-mL) maintains durable improvement across multiple treatment cycles

Abstract: Background: Cervical dystonia (CD), the most common focal dystonia, is a chronic neurological movement disorder characterized by sustained involuntary contractions of the neck muscles, leading to abnormal postures. AbobotulinumtoxinA (aboBoNT-A) was approved in the US initially as a 500 U per 1-mL dilution and subsequently, as a 500 U/2-mL dilution (or 250 U/mL), thereby providing clinicians with more flexible dosing options to better meet individual patient needs. The objective of this open-label extension st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Search terms used were abobotulinumtoxinA or Dysport, cervical dystonia or spasmodic torticollis, and pain. Four studies and their open label extensions were identified [68][69][70][71][72][73] and we obtained the patient level data from the study sponsors associated datasets. Changes from baseline to Week 4 and Week 12 in TWSTRS pain scores were assessed using an ANCOVA with treatment as fixed effect, baseline values as covariates, and subject as random effect.…”
Section: Management With Botulinum Toxin Including a Meta-analysis Of Controlled Clinical Trial Data For Abobotulinumtoxina In The Managementioning
confidence: 99%
“…Search terms used were abobotulinumtoxinA or Dysport, cervical dystonia or spasmodic torticollis, and pain. Four studies and their open label extensions were identified [68][69][70][71][72][73] and we obtained the patient level data from the study sponsors associated datasets. Changes from baseline to Week 4 and Week 12 in TWSTRS pain scores were assessed using an ANCOVA with treatment as fixed effect, baseline values as covariates, and subject as random effect.…”
Section: Management With Botulinum Toxin Including a Meta-analysis Of Controlled Clinical Trial Data For Abobotulinumtoxina In The Managementioning
confidence: 99%